Biologically active compounds from selected aphyllophorales mycelial cultures - Sułkowska-Ziaja, Katarzyna; Muszyńska, Bożena; Firlej, Anna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
For a long time fungi belonging to Basidiomycota phylum have been in the center of attention because of the presence in their fruiting bodies of compounds with known therapeutic activity. Mycelial cultures of two aphyllophorales species occurring in Poland, Hydnum repandum L., and Sparassis crispa (Wulf.) Fr., were analyzed in our study. The main aim of the study was qualitative and quantitative analysis of extracts obtained from the mycelial cultures for the presence of known biologically active compounds, including phenolic acids, non-hallucinogenic indole compounds and sterols. For analyses a reversed-phase chromatography (RP-HPLC) method was used. The presence of eight phenolic acids including gallic, gentisic, p-hydroxybenzoic, caffeic, p-coumaric protocatechuic, syringic, vanillic and cinnamic acids was confirmed in the extracts obtained from the biomass. The quantitatively predominant metabolites in biomass from in vitro cultures of H. repandum and S. crispa were protocatechuic acid (6.23 μg/g DW) and p-hydroxybenzoic acid (4.52 μg/g DW). Derivatives of indole such as indole, serotonin, tryptamine and tryptophan were measured quantitatively. Their total content was estimated as 1.28 μg/g DW and 3.07 μg/g DW in H. repandum and S. crispa extracts, respectively. The major metabolite found was tryptophan. In addition, ergosterol, one of the sterols present in the biomass of in vitro cultures of S. crispa was analyzed (700.87 μg/g DW). The obtained results confirm the hypothesis that mycelial cultures of domestic species of aphyllophorales are able to accumulate biologically active metabolites.